The operational concept of Mini LNG Carrier: Preventing sedimentation on the seabed. Issue 1 (1st September 2022) - Kadir, Abdul; Istadi, I.; Iskendar, I.; Subagio, Agus; Ali, Baharuddin; Nurcholis, N.; Waluyo, W.
Abstract: Utilization Mini LNG Carrier is an alternative solution to support the supply chain for the distribution of liquefied natural gas (LNG) to gas power plants, especially in Eastern Indonesia. Mini LNG carriers must have adequate seakeeping and manoeuvrability in carrying out their missions. The biggest challenge faced when manoeuvring in shallow water where the rotation of the propeller can produce high-velocity water flows that cause sedimentation on the seabed. The distance between the tip of the propeller to the seabed greatly determines the level of ease of erosion and sedimentation that can occur. This study aims to provide an alternative ships' operational concept by mapping the suitability between the depth of the water and the rpm of the propeller that does not cause sedimentation on the seabed. This concept determines the velocity of the water flow at which sedimentation begins to occur as the propeller rpm threshold. The final result is a depth division map where the propeller can be used at maximum rpm, the propeller is used with a limited rpm and the depth at which the propeller is not recommended to be used.